Prawo do bycia zapomnianym w perspektywie przetwarzania danych osobowych - Nasiadka, Łukasz (Studia Prawa Publicznego, 2023)
Nowadays, effective protection of personal data is one of the fundamental issues of a democratic state under the rule of law. Therefore, the legislator should be very precise about the principles and standards of data processing. In the last few decades, in particular, the development of new technologies, digitalisation and the increase in the need for electronic communication has become evident, which leads to the adoption of appropriate regulations for the handling of personal data. In addition, the EU legislator has introduced the General Data Protection Regulation (GDPR) in order to harmonise the regulations of EU Member States regarding the protection of personal data. This provides a framework for the proper functioning of legal provisions across the European Union regarding the handling of personal data of its citizens. The aim of the article is to identify the legal changes resulting from the Personal Data Protection Regulation, with a particular focus on the persons to which they apply and then to analyse the regulation of ‘the right to be forgotten’. In the first part of the article, attention is drawn to the way personal data are processed and the scope of obligations incumbent on data controllers. This is because data controllers are, together with the personal data protection officer, responsible for recording data processing activities, including ongoing monitoring and responding to situations of inaccurate data processing. The second part focuses on the right to be forgotten and the assessment of this entitlement in the perspective of Regulation 2016/679. The research methods include an analysis of legal acts, at the same time using the subject literature.